2019
DOI: 10.1093/gerona/glz248
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Developing a Discordance Index for Older Adults With Chronic Kidney Disease

Abstract: Background Older adults with chronic kidney disease (CKD)-discordant conditions (comorbid conditions with treatment recommendations that potentially complicate CKD management) have greater risk of hospitalization and death. Our goal was to develop a CKD-Discordance Index using electronic health records to improve recognition of discordance. Methods This retrospective cohort included Kaiser Permanente Southern California patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 40 For example, in a study of 436 Dutch individuals with CKD, over 80% reported weakness and one third had pain. 41 Although multiple medical conditions, often referred to as multimorbidity, has received much attention, 42 including in persons with CKD, 43 45 the presence of multiple geriatric syndromes in older adults has been relatively limited. Using cross-sectional Health and Retirement Study data, Cigolle et al found that older adults with multiple geriatric syndromes were more likely to have difficulties with activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“… 40 For example, in a study of 436 Dutch individuals with CKD, over 80% reported weakness and one third had pain. 41 Although multiple medical conditions, often referred to as multimorbidity, has received much attention, 42 including in persons with CKD, 43 45 the presence of multiple geriatric syndromes in older adults has been relatively limited. Using cross-sectional Health and Retirement Study data, Cigolle et al found that older adults with multiple geriatric syndromes were more likely to have difficulties with activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies have shown that older adults with advanced CKD are at risk for functional decline, less is known about what contributes to their functional loss. One possibility is that older adults with advanced CKD commonly experience health stressors, including illnesses or injuries that require an acute care encounter such as an emergency department (ED) visit or hospitalization, and these events result in functional impairment [ 7 9 ]. One’s capacity to respond before a health stressor and the trajectory of functional recovery afterwards are described by the emerging geriatric concepts of reserve and resilience, respectively [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CKD is usually accompanied by multiple comorbidities including type 2 diabetes, hypertension, and obesity [1,3], and individualized therapies to manage each comorbidity may not be concordant, which may frustrate the patient. Moreover, patients with CKD who receive discordant treatment recommendations owing to conditions that potentially complicate CKD management-for example, health failure or cancer-or because of having multiple medication prescribers have higher risk of health care usage and mortality [4].…”
Section: Introductionmentioning
confidence: 99%